Friction Performonce Anolysis of woste Tire Rubber Powder Reinforced polypropylene using pin-on-Disk Tribometer - Sivarao, Subramonian; Qumrul, Ahsan; Mohd Amran, Md Ali; T.J.S, Anand; RAJA ABDULLAH, RAJA IZAMSHAH; Aziz, Alif (2013)
Corbon nonotube reinforced oluminium nono-composites powder were produced using metollurgy route wiih different weight percent of cNT into the At mohix. The weor behoviour of pure aluminium (Al) ond corbon nonolube reinforced aluminium (CNT-A|) nono-cornposite with different CNT content were studied with o pin-on-disc tribometer, sliding against AlSl52l00 steel disc. Experiments were conducted using different sliding velocities of 0.5, 0.65 ond O.7g m/s and a normal load of 5.5, 7.2 ond l0 N. From the wear map it is observed that, during dry sliding wear on increase of any of the operating condition such os normal applied load, sliding velocity, or duration of rubbing leads at some stage to a sudden change in the wear rote (weight loss per sliding distance).